[Rezension von: Pruitt, Nicholas T., Open hearts, closed doors] - Drake, Janine Giordano; Pruitt, Nicholas T. (2023)
Over the last several decades of scholarship in Evangelical Studies, few books have directly addressed the topic of evangelicals’ attitudes toward immigration. When we consider the multiplicity of church ministries, mainline and evangelical, which have catered to immigrants and refugees over the last century, this relative silence is even more peculiar. How did American Protestants think about immigration and immigration restriction over the previous century and why haven’t we spent much time exploring the topic?In his new book, Open Hearts, Closed Doors, Nick Pruitt takes on the first question and gives us tools to answer the second. The book shows that while white mainline Protestants embraced or accepted immigration restriction between 1921 and 1965, many were also welcoming to the trickle of immigrants that did arrive in the United States. As Pruitt tells the story, mainline Protestant churches maintained many facets of their "Americanization" oriented ministries which were built during the height of the Social Gospel era. When severe restrictions according to national origins became law, mainline Protestants continued these ministries and gradually embraced a modicum of what Pruitt calls "cultural pluralism." Many, Pruitt notes, even advocated for US participation in refugee resettlement programs, as well as opening migration to Japan and China. In these white Protestants’ worldview, Pruitt argues, a "manageable" number of newcomers could be assimilated into the "melting pot" that was the United States. This gradualist posture helped prepare these white Protestants to accept the loosening of immigration restriction policies in 1965.
Keywords: Rezension